Indonesian Millennial Awareness to Privacy and Personal Data Protection on the Internet - Noor, Muhammad Usman (DESIDOC Journal of Library & Information Technology, 2020)
The internet is the daily consumption of millennials. The internet in addition to having extensive benefits in a variety of ways, howevera violation of privacy and personal datacould haunt them. Various forms of violations of privacy and personal data can harm and endanger the internet users, so that sufficient awareness and understanding is needed to be able to minimise these risks. This study aims to describe the recognition and response of the Indonesian millennials to protect their personal data, including what personal data needs to be protected most, behaviour on the internet towards personal data, and respond to problems of personal data violations. This study uses a quantitative approach. The data collection method used is an online questionnaire that is distributed to millennial generations. The analytical method used is descriptive analysis. The results of this study indicate that the millennial generation considers personal data that is closely related to family and their owns have to be protected. Millennials also show suspicious behaviour regarding their personal data on the internet and assume that all forms of violation of privacy and personal data are disturbing and offensive. This research is open to being developed further, among others by looking at and measuring the competence of millennials and what factors determine the success of protecting personal data on the internet.